Sosial, Politik, dan Ekonomi Kesejahteraan Sosial: Refleksi Demokrasi dan Fenomena Sosial Indonesia - Reza Ardiansyah Pradana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2020)
In an effort to understand social welfare, a multidimensional framework from a social, political and economic perspective is needed. The social perspective will show how society on an individual and community basis is an important part of social welfare studies. With sociological approaches such as Max Weber and Pierre Bourdieu in the analysis of society and even politics, this paper shows that anthropology in seeing the phenomenon of welfare is not quite right. Then in the realm of politics, this paper seeks to present the side of public policy and social policy resulting from the political process and how democracy works in its transition and circumstances. The economy is seen from both global and local perspectives as a reality of the world phenomena that have occurred regarding the 1997 and 2008 recessions, then the neoliberalism regime, and then how the alternative welfare proposed by some thinkers is presented in this paper.